Wear behavior of PVD and CVD coated carbide tools when face milling Inconel 718 - Jawaid, A.; Koksal, S.; Sharif, S. (Tribology Transaction, 2000)
The wear behavior of two types of coated cemented carbide tools has been studied when face milling a nickel-based superalloy Inconel 718. PVD-TiN and CVD-TiCN+Al2O3 tools were used. It was found that the coatings were detached after only five seconds of cutting. An attrition type wear mechanism associated with workpiece material adhesion was observed which eventually led to severe chipping, flaking, plastic deformation and cracking. It was noted that the coatings had no significant effect on tool performance under the cutting conditions tested.